The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1469-8137.2007.02077.x
|View full text |Cite
|
Sign up to set email alerts
|

Parallel evolution of dwarf ecotypes in the forest tree Eucalyptus globulus

Abstract: Three small populations of a dwarf ecotype of the forest tree Eucalyptus globulus are found on exposed granite headlands in south-eastern Australia. These populations are separated by at least 100 km. Here, we used 12 nuclear microsatellites and a chloroplast DNA marker to investigate the genetic affinities of the dwarf populations to one another and to their nearest populations of tall E. globulus. Cape Tourville was studied in greater detail to assess the processes enabling the maintenance of distinct ecotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 53 publications
2
95
1
Order By: Relevance
“…The results of Carnegie and Ades (2005) also indicated that higherelevation inland populations may exhibit less resistance than nearby coastal populations in eastern and south-eastern Tasmania. Adaptive responses over fine geographic scales in E. globulus, have been reported in terms of the parallel evolution of dwarf ecotypes and in patterns of genetic variation in drought tolerance (Dutkowski and Potts, 2012;Jordan et al, 2000;Foster et al, 2007). Variation in MLD resistance over hundreds of metres has also been observed between ecologically distinct E. obliqua populations along topographic gradients, with the more resistant germplasm derived from more closed forest sites, which are more likely to have high disease risk (Wilkinson, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…The results of Carnegie and Ades (2005) also indicated that higherelevation inland populations may exhibit less resistance than nearby coastal populations in eastern and south-eastern Tasmania. Adaptive responses over fine geographic scales in E. globulus, have been reported in terms of the parallel evolution of dwarf ecotypes and in patterns of genetic variation in drought tolerance (Dutkowski and Potts, 2012;Jordan et al, 2000;Foster et al, 2007). Variation in MLD resistance over hundreds of metres has also been observed between ecologically distinct E. obliqua populations along topographic gradients, with the more resistant germplasm derived from more closed forest sites, which are more likely to have high disease risk (Wilkinson, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…In a genetic study of E. globulus, this usually tall forest tree has recurrently given rise to a dwarf ecotype found parapatrically on coastal cliffs ( Foster et al 2007). However, if Metrosideros bog growth forms are repeatedly derived from non-bog forms, an indigenous origin of bog plants from surrounding areas on the same island would seem more likely.…”
Section: Results (A) Phylogenetic and Comparative Analysesmentioning
confidence: 99%
“…Evidence that divergent selection has shaped population divergence in functional traits (or fitness surrogates) arises when (i) population differentiation is higher than expected based on drift (Q st > F st ) and (ii) there Gosney et al 2016), as well as disease ) and drought susceptibility (Dutkowski & Potts 2012). There is also evidence that the ontogenetic timing of transition to adult foliage and the onset of flowering are adaptive, although the broad-scale association with climate may be non-linear (Jordan et al 2000;Foster et al 2007). In E. pauciflora Sieber ex Spreng., glasshouse trials of 37 Tasmanian provenances found that the mean maximum temperature of the site of origin was the most significant climate variable associated with provenance divergence.…”
Section: Climate-related Genetic Variation In Functional Traitsmentioning
confidence: 99%